1975
DOI: 10.1111/j.1399-0004.1975.tb01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis associated antigen and the ABO locus in Down's syndrome

Abstract: The recent observation by Arndt-Hansen et al. (1974) of increased frequency of blood group A over group 0 in blood donors positive for the hepatitis associated antigen has been investigated in Down's syndrome, in order to establish if this could account for the increased frequency of the antigen in that syndrome.Seventy-one of 227 subjects with Down's syndrome (31.3 %) were found to be positive for the antigen by haemagglutination, and comparison of these with the HAA-subjects failed to reveal any differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…On the other hand, among confirmed HBsAg carrier blood donors, group‐A was significantly less common in HBeAg‐positive donors than in the total carrier population, but the distribution of ABO group was similar to that of the general population . There are also other studies that found no significant differences in the ABO distribution between asymptomatic AA carriers or patients with chronic hepatitis B with controls in normal and in subjects with Down's syndrome . In this study, regression analysis confirmed that it was groups‐B and ‐AB, but not Rh D negativity, that were independently associated with increased HBV infection.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, among confirmed HBsAg carrier blood donors, group‐A was significantly less common in HBeAg‐positive donors than in the total carrier population, but the distribution of ABO group was similar to that of the general population . There are also other studies that found no significant differences in the ABO distribution between asymptomatic AA carriers or patients with chronic hepatitis B with controls in normal and in subjects with Down's syndrome . In this study, regression analysis confirmed that it was groups‐B and ‐AB, but not Rh D negativity, that were independently associated with increased HBV infection.…”
Section: Discussionsupporting
confidence: 74%
“…While providing a selective advantage against severe malaria, the group‐O phenotype increases the severity of cholera infection and susceptibility to gastrointestinal infection by E. coli O157 and H pylori (O Le group) . For viral infections, secretors of the ABH and Le antigens have greater susceptibility to influenza viruses, rhinoviruses, respiratory syncytial virus and echoviruses , but the relationship with HBV infection remains inconclusive . As for the Rh phenotypes, which reflect genetic drift and migration , no association with serum hepatitis was found , although in volunteer blood donors, Rh D positivity was significantly higher among HBV carriers .…”
Section: Introductionmentioning
confidence: 99%